An estimation of remaining life expectancy of generator step-up transformer based on strength analysis of insulating paper - Surin Sermsukroongsakul (2018)
© 2017 IEEE. This article presents a lifetime study of oil immersed Generator Step-Up (GSU) transformers and their remaining life expectancy which are investigated in Electricity Generation Authority of Thailand (EGAT). The GSU transformer remaining life depends on its solid insulation. The analysis of insulation strength and statistical data are applied for lifetime curve model. By this evaluation method, it can assess a remaining life of GSU transformer and maintain reliability of electric generation system. In addition, this method can support Power Development Plan (PDP) strategy to prolong the lifetime of some power plants. The lifetime curve of GSU transformers are assessed and compared with the previous study for the grid transformer lifetime.